Leverage, Accruals-based Earnings Management, Real Earnings Management and Firm Performance: The Stock Exchange of Thailand - Pithaktum, Natthinee; Petchchedchoo, Pattannan; Kumsuprom, Siridech; Wilalai, Premarat (Rajapark Journal, 2025)
This research aims to study the influence of leverage on earnings management, the influence of earnings management on performance, and the influence of leverage on performance through the influence of earnings management of listed companies in the Stock Exchange of Thailand, which were significantly affected during the COVID-19 pandemic. The data used in this study is secondary data from the annual financial statements (SET Smart) and Form 56-1 for the years 2020-2022, covering 139 companies quarterly, totaling 1,668 data points. Path analysis and structural equation modeling were used for statistics analysis. The results of the study show that the debt-to-equity ratio and the debt-to-assets ratio influence earnings management in various ways, especially short-term debt, which affects earning management through both accrual-based and real earnings management. However, the performance of companies does not appear to be directly influenced by earnings management, indicating the strength of the Thai capital market’s governance structure during the crisis. It is recommended that regulatory authorities develop policies that promote transparency during crises and increase comparative studies on the effects of earnings management across different industry sectors in the future.